Structure and stress state of TiN and Ti₀.₅₋xAl₀.₅YxN coatings prepared by the PIII&D technique from filtered vacuum-arc plasma - Reshetnyak, E.N. (Вопросы атомной науки и техники, 2014)
The results of investigations of the structure and stress state of TiN and Ti₀.₅₋xAl₀.₅YxN coatings deposited from the filtered vacuum-arc plasma under high voltage pulsed bias potential on the substrate are presented. It was found that axial texture [110] is formed in coatings when pulses potential with an amplitude 0.5…2.5 kV are applied. For TiN coatings with increasing amplitude of the potential the perfection of texture is increased and the level of residual compressive stress is decreased. As for Ti₀.₅₋xAl₀.₅YxN coatings with increasing amplitude the stress level is increased. In this case the texture is most strong outlined at the amplitude of 1 kV. With further increase in the amplitude the texture perfection becomes weaker. Differences of structure and stress state may occur due to the possibility of phase transition for multi-component coatings Ti-Al-Y-N associated with the decay of the supersaturated solid solution (Ti,Al)N stimulated by high energy ion bombardment. Приведены результаты исследований структуры и напряженного состояния TiN- и Ti₀.₅₋xAl₀.₅YxN-покрытий, полученных из фильтрованной вакуумно-дуговой плазмы при подаче высоковольтного импульсного потенциала смещения на подложку. Обнаружено, что при амплитуде импульсного потенциала 0,5…2,5 кВ в покрытиях формируется аксиальная текстура [110]. Для TiN-покрытий с ростом амплитуды степень совершенства текстуры растет, а уровень остаточных напряжений сжатия падает. Для покрытий Ti₀.₅₋xAl₀.₅YxN с ростом амплитуды уровень напряжений увеличивается. При этом наиболее совершенная текстура наблюдается при амплитуде 1 кВ. При дальнейшем увеличении амплитуды степень совершенства текстуры уменьшается. Различия структуры и напряженного состояния покрытий могут быть обусловлены возможностью фазового перехода в многокомпонентных покрытиях Ti-Al-Y-N, связанного с распадом пересыщенного твердого раствора (Ti, Al)N под действием высокоэнергетичной ионной бомбардировки Наведено результати досліджень структури і напруженого стану TiN- та Ti₀.₅₋xAl₀.₅YxN-покриттів, отриманих з фільтрованої вакуумно-дугової плазми при подачі високовольтного імпульсного потенціалу зміщення на підкладку. Виявлено, що при амплітуді імпульсного потенціалу 0,5…2,5 кВ у покриттях формується аксіальна текстура [110]. Для TiN-покриттів із зростанням амплітуди потенціалу ступінь досконалості текстури зростає, а рівень залишкових напружень стиснення падає. Для покриттів Ti₀.₅₋xAl₀.₅YxN із зростанням амплітуди рівень напружень збільшується. При цьому найбільш досконала текстура спостерігається при амплітуді 1 кВ. При подальшому збільшенні амплітуди ступінь досконалості текстури зменшується. Відмінності структури і напруженого стану покриттів можуть бути обумовлені можливістю фазового переходу в багатокомпонентних покриттях Ti-Al-Y-N, пов'язаного з розпадом пересиченого твердого розчину (Ti, Al)N під впливом високоенергетичного іонного бомбардування.